Cardiovascular Risk and Metabolic Syndrome Characteristics in Patients with Nonfunctional Pituitary Macroadenoma - Guadalupe Vargas-Ortega; Baldomero González-Virla; Lourdes Balcázar-Hernández; Oriana Nieto-Guzmán; Ana Pamela Garrido-Mendoza; Marco Antonio Flores-Maya; Victoria Mendoza-Zubieta (International Journal of Endocrinology)
Context. An elevated incidence of type 2 diabetes and cardiovascular disease (CVD) has been reported in patients with nonfunctional pituitary macroadenoma (NFPMA). There is no information about metabolic syndrome and cardiovascular risk in patients with NFPMA in our population. Objective. Analyze the metabolic syndrome (MetS) components and estimate cardiovascular risk in patients with NFPMA. Design and Setting. Retrospective study, at the tertiary care center. Patients and Methods. 71 patients with NFPMA treated according to a preestablished multimodal protocol. Main Outcome Measures. Prevalence of diabetes, hypertension, high cholesterol, obesity, and cardiovascular risk and its relationship with the clinical and biochemical characteristics. Results. The prevalence of diabetes, hypertension, high cholesterol, and obesity at diagnosis was 30%, 27%, 48%, and 85% and did not change upon the last visit. The prevalence of MetS changes from 54 to 48% (p=0.001). NFPMA patients showed a significant increase risk for high total cholesterol (SMR 1.68, 95% CI 1.28–2.17, p=0.001) and diabetes (SMR 3.19, 95% CI 2.19–4.49, p=0.01). According to Globorisk, the male gender was an evidence of high CVD before (81% versus 18%, p=0.01) and after (72% versus 28%, p=0.01) multimodal treatment. Conclusion. A high prevalence of cardiovascular and metabolic disease and a high cardiovascular risk were evidenced in patients with NFPMA, especially in men. Risk factors such as the personal history of hypertension and dyslipidemia could explain the foregoing, so the control and treatment of metabolic parameters and cardiovascular risk should be an integral part of the follow-up of these patients.